Efficacy of pre- and post-emergence herbicide combinations on weed control in no-till mechanically transplanted rice - Mitra, Biplab; Patra, Koushik; Bhattacharya, Prateek Madhab; Ghosh, Arunava; Chowdhury, Apurba Kumar; Dhar, Tapamay; Islam, Saiful; Laing, Alison M.; Gathala, Mahesh Kumar (Informa UK Limited, 2022)
No-till mechanized-transplanted rice was evaluated for different combinations of pre- and post-emergence herbicides to determine feasible, economically viable weed management options to control complex weed flora in rice fields. All pre-emergence herbicides significantly reduced the population of grassy weeds; of these, pendimethalin resulted in the greatest reductions (83%) at 15 days after transplanting (DAT). Among five post-emergence herbicide treatments, the combination of bispyribac-sodium (10%SP) + pyrazosulfuron (10%WP) was found to be the most effective in controlling all weed flora at both 35 and 55 DAT. The sequential application of pendimethalin (pre-emergence) followed bispyribac-sodium + pyrazosulfuron (post-emergence) resulted in significantly higher rice grain yield (4.4 t-ha−1) and relative gross-margin (417 USD-ha−1) than all other treatments. A strong negative correlation was observed between rice grain yield and weed biomass, and a strong positive correlation between rice grain yield and weed control efficiency. Our findings demonstrate the potential to combine pre- and post-emergence herbicides in no-till mechanized-transplanted rice; these findings have applications globally in regions where rice is established by no-till or mechanized transplanting.